2018
DOI: 10.4314/sajas.v48i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Survival and development of embryos of <i>Gallus gallus domesticus</i> treated with inorganic bromide

Abstract: The range of bromide (Br-) in groundwater sources surveyed in South Africa is 0-18.4 mg/L. The research aimed to establish chicken embryo sensitivity to a range of Br treatments (mg/L) injected into fertilised Ross-308 eggs in three phases: (1) five eggs injected with 10 mg Br-/L; (2) 45 eggs divided into groups and injected with 0, 1 and 5 mg Br-/L; (3) 148 eggs divided into groups injected with 0, 0.01, 0.05, 0.5, and 1 mg Br-/L. Incubation was at standard conditions. Breakout analysis was done at various st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This decreasing ratio, aligned with the lower liver mass and increased heart mass, indicated that the higher levels of NanoZnO may induce differential organ development in chicken embryos. Chicken embryos are highly sensitive models for testing potential toxic effects of injected substances by monitoring total and differential organ development rates and survivability of the embryos (Korhonen et al, 1982;Sawosz et al, 2014;Lucht et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This decreasing ratio, aligned with the lower liver mass and increased heart mass, indicated that the higher levels of NanoZnO may induce differential organ development in chicken embryos. Chicken embryos are highly sensitive models for testing potential toxic effects of injected substances by monitoring total and differential organ development rates and survivability of the embryos (Korhonen et al, 1982;Sawosz et al, 2014;Lucht et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Lucht et al (2018), having tested concentrations of Br that was injected into fertilized chicken (Gallus gallus domesticus) eggs, reported that Br is toxic to embryos at 1 mg/L and lethal at concentrations that are greater than 1 mg/L. Embryo survival was significantly negatively correlated (R 2 = -0.92) with increasing Br concentrations.…”
Section: Text Box 1 Guide To Water Quality Constituents Risk Assessmentmentioning
confidence: 99%